Co-housing with Tibetan chickens improved the resistance of Arbor Acres chickens to Salmonella enterica serovar Enteritidis infection by altering their gut microbiota composition - Qianyun Zhang; Qidong Zhu; Yunqi Xiao; Qinghua Yu; Shourong Shi (Journal of Animal Science and Biotechnology)
Abstract Background Salmonella enterica serovar Enteritidis (S. Enteritidis) is a global foodborne pathogen that poses a significant threat to human health, with poultry being the primary reservoir host. Therefore, addressing S. Enteritidis infections in poultry is crucial to protect human health and the poultry industry. In this study, we investigated the effect of co-housing Arbor Acres (AA) chickens, a commercial breed susceptible to S. Enteritidis, with Tibetan chickens, a local breed resistant to S. Enteritidis infection, on the resistance of the latter to the pathogen. Results Ninety-six 1-day-old Tibetan chickens and 96 1-day-old AA chickens were divided into a Tibetan chicken housed alone group (n = 48), an AA chicken housed alone group (n = 48), and a co-housed group (48 birds from each breed for 2 cages). All birds were provided the same diet, and the experimental period lasted 14 d. At d 7, all chickens were infected with S. Enteritidis, and samples were collected at 1-, 3-, and 7-day-post-infection. We found that the body weight of AA chickens significantly increased when co-housed with Tibetan chickens at 1- and 3-day-post-infection (P < 0.05). In addition, the cecal S. Enteritidis load in AA chickens was significantly reduced at 1-, 3-, and 7-day-post-infection (P < 0.05). Furthermore, the inflammatory response in AA chickens decreased, as evidenced by the decreased expression of pro-inflammatory cytokines NOS2, TNF-α, IL-8, IL-1β, and IFN-γ in their cecal tonsils (P < 0.05). Co-housing with Tibetan chickens significantly increased the height of villi and number of goblet cells (P < 0.05), as well as the expression of claudin-1 (P < 0.05), a tight junction protein, in the jejunum of AA chickens. Further analysis revealed that co-housing altered the gut microbiota composition in AA chickens; specifically, the relative abundances of harmful microbes, such as Intestinimonas, Oscillibacter, Tuzzerella, Anaerotruncus, Paludicola, and Anaerofilum were reduced (P < 0.05). Conclusions Our findings indicate that co-housing with Tibetan chickens enhanced the resistance of AA chickens to S. Enteritidis infection without compromising the resistance of Tibetan chickens. This study provides a novel approach for Salmonella control in practical poultry production.